Joint ruin probability and risk contagion measure in a quota-share reinsurance risk model: An asymptotic approach - Yang, Yang; Huang, Rongshan; Meng, Hui (Nonlinear Analysis: Modelling and Control, 2026)
Consider a quota-share reinsurance risk model with constant premiums and stochastic returns in which an insurer purchases fixed-proportion quota-share reinsurance for its business line. Both the insurer and reinsurer may engage in risk-free investments, with their nonnegative general (not necessarily Lévy) log-price processes following an arbitrary dependence structure. Under the assumption that claim sizes are pairwise strongly quasiasymptotically independent and follow heavy-tailed distributions, this paper derives asymptotic formulas for two types of finite-time joint ruin probabilities and for a risk contagion measure from the insurer to the reinsurer. Furthermore, we conduct numerical studies to verify the accuracy of the derived asymptotic results, using the Monte Carlo method combined with an explicit order-3.0 weak scheme.
Keywords: asymptotics; quota-share reinsurance risk model; finite-time joint ruin probability; risk contagion measure; explicit order-3.0 weak scheme